Maioriano, la plebe e il defensor civitatis - Oppedisano, Fabrizio (Rivista di Filologia e di Istruzione Classica, 2011)
Abstract This article analyzes Majorian’s novella 3, whereby the role of the defensor civitatis was re-established in the West. The text sheds light upon Majorian’s political insight and his commitment to legislation that was aimed at lessening the iniquities and disparities that affected the lower classes. In this law we find significant evidence for the evolution of the defensor civitatis and, more generally, the administration of the city in the fifth century. In particular, the text reveals the active role exercised by the plebs in appointing the defensores.